Languages of Modern Jewish Cultures : Comparative Perspectives - Kronfeld, Chana; Miller, Joshua L., 1971-; Norich, Anita, 1952- (Book collections on Project MUSE., 2016)
"As trends in Jewish Studies have turned attention to transnationalism, globalization, and hybrid cultures, the moment for a major new collection of essays redefining the conceptual frameworks of Jewish Language Studies is now. Languages of Modern Jewish Cultures collects work from the most prominent scholars in the field, bringing world literary and linguistic perspectives to generate distinctively new historical, cultural, theoretical, and scientific approaches to this topic of ongoing interest. The chapters of this edited volume consider, from multiple angles, the cultural politics of the myths, fantasies, and anxieties of linguistic multiplicity in the history, cultures, folkways, and politics of global Jewry. Jewish lingualisms may offer models for more precise conceptualizations of what we mean by multiculturalism, as residues of social interaction grounded in the lived experiences of Jews of divergent times and locations. Methodological range is as important to this project as linguistic range. Thus, in addition to approaches that highlight influence, borrowings, or acculturation, the volume represents those that highlight syncretism, the material conditions of Jewish life, and comparatist perspectives. "--publisher's website